Technology In America : - Marcus, Alan I. (Harcourt Brace College Publishers, 1999)
Now in a thoroughly updated new edition, this successful textbook surveys the history of technology and the role it has played in the social, cultural, political and economic development of the American nation, from the 1600s to the 21st century. With new content on globalisation, Native American technologies, women and gender, and environment.